Taxi! : A Social History of the New York City Cabdriver - Hodges, Graham Russell (Book collections on Project MUSE., 2007)
"Taxi! is the first book-length history of New York City cabdrivers and the community they compose. From labor unrest and racial strife among cabbies to ruthless competition and political machinations, this narrative captures the people - lower-class immigrants for the most part - and their hardscrabble struggle to capture a piece of the American dream. Graham Russell Gao Hodges tells their tale through contemporary news accounts, Hollywood films, social science research, and the words of the cabbies themselves."--Jacket.